2020
DOI: 10.1093/mnras/staa446
|View full text |Cite
|
Sign up to set email alerts
|

The origin of dust in galaxies across cosmic time

Abstract: We study the dust evolution in galaxies by implementing a detailed dust prescription in the SAGE semi-analytical model for galaxy formation. The new model, called Dusty SAGE, follows the condensation of dust in the ejecta of type II supernovae and asymptotic giant branch (AGB) stars, grain growth in the dense molecular clouds, destruction by supernovae shocks, and the removal of dust from the ISM by star formation, reheating, inflows and outflows. Our model successfully reproduces the observed dust mass functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 86 publications
(191 reference statements)
5
74
0
Order By: Relevance
“…There is an increasing trend of dust-to-gas ratio with decreasing redshift, but the evolutionary track on the tot -is almost invariant. This is consistent with other theoretical models of dust enrichment in cosmological simulations by Hou et al (2019) (at 2) and Li et al (2019), and the semi-analytic model of Popping et al (2017) and Triani et al (2020) (although Vijayan et al 2019 showed an additional dependence on the stellar age). The tight tot -relation is also compatible with the analytical result that metallicity is the main driver of dust enrichment (Inoue 2011).…”
Section: Dust-to-gas Ratio and Metallicitysupporting
confidence: 90%
“…There is an increasing trend of dust-to-gas ratio with decreasing redshift, but the evolutionary track on the tot -is almost invariant. This is consistent with other theoretical models of dust enrichment in cosmological simulations by Hou et al (2019) (at 2) and Li et al (2019), and the semi-analytic model of Popping et al (2017) and Triani et al (2020) (although Vijayan et al 2019 showed an additional dependence on the stellar age). The tight tot -relation is also compatible with the analytical result that metallicity is the main driver of dust enrichment (Inoue 2011).…”
Section: Dust-to-gas Ratio and Metallicitysupporting
confidence: 90%
“…In addition, 47 sources (15% of the total sample) form their stellar masses at very short timescales of 100 Myr. Studying the evolution of galaxies in the SAGE semi-analytical model, Triani et al (2020) have found that the grain growth starts to dominate overall dust production if 12 + log(O/H) 8.5 and log(M /M ) 9.2. Here, 84% of our sources fulfil both of these criteria, which implies that the dust grain growth in ISM would be the dominant source of dust production in the vast majority of observed DSFGs.…”
Section: Modelling the Observed Evolution Of M Dust /Mmentioning
confidence: 99%
“…The SFR, , is not in general a function of the other model parameters, as galaxies grow and evolve due to the accretion and ejection of gas, and occasional mergers (Nanni et al 2020;Triani et al 2020). We assume…”
Section: Star Formationmentioning
confidence: 99%
“…Some studies of dust evolution (e.g. Triani et al 2020) do use a metallicity-dependent destruction efficiency, but to our knowledge, the impact of such an evolving efficiency has not been investigated in detail. In this paper, we show that an increasing destruction efficiency at low metallicity E-mail: priestleyf@cardiff.ac.uk may remove the tension between high stellar dust yields and the low DTM ratios seen in some galaxies, if the dependence on metallicity is strong enough.…”
mentioning
confidence: 99%